Exploring determinants of, and interventions for, delayed presentation of women with breast symptoms: A systematic review. (February 2020) - Kailemia, Peter N.; Lee, Elaine C.; Taylor, Cara; Renfrew, Mary J.
Abstract: Purpose: Behaviour change interventions are more likely to be effective if they are sensitive to contextual determinants of behaviour. Delayed presentation of women with breast symptoms is a concern for both high-income and low- and medium-income countries. Our aim was to integrate evidence on determinants of time to presentation of women with breast symptoms with complementary evidence on interventions for promoting early presentation. Methods: A systematic review was conducted according to PRISMA guidelines. Ten electronic databases were searched for relevant articles published between 1985 to May 2019. Pre-defined selection criteria were applied to retrieved records. Evidence on interventions, and on determinants were integrated through sequential explanatory synthesis design. Results: Of the 4185 documents retrieved, 11 intervention studies and 10 determinants studies were included in the synthesis. Overall, evidence on interventions is of low quality, while that on determinants is of medium quality. Intervention studies were mostly individual-level with almost exclusive focus on breast cancer awareness among postmenopausal women in high-income countries. Synthesis of evidence on determinants resulted in 10 domains. Juxtaposing the evidence on determinants of time to presentation of women with breast symptoms with that of the interventions to promote early presentation shows a mismatch between them. Conclusions: Whilst t here is strong evidence that women with breast symptoms face multi-level influences to presentation, current interventions have focused almost exclusively on breast cancer awareness in high-income countries. High quality multi-level interventions are required to promote early presentation of symptomatic women in different socio-cultural and economic settings. Highlights: Women with breast symptoms delay help-seeking and interventions have been developed to promote their early presentation. It is not known if the current interventions match with multi-level determinants of symptomatic women's help-seeking behaviour. Current interventions for promotion of early presentation of women with breast symptoms are mostly individual-level with almost exclusive focus on postmenopausal women in high-income countries. There is a mismatch between determinants of time to presentation of women with breast symptoms, and interventions to address them. There is a dearth of high quality evidence on multi-level interventions to promote early presentation of women with breast symptoms.